Environmental Impact of Freight Transportation in Cd. Juarez region and Review of Aerodynamic Drag Reduction Devices for Heavy Trucks - Tilvaldyev, Shehret (IJSES, 2019)
http://ijses.com/wp-content/uploads/2019/11/47-IJSES-V3N10.pdf